2002
DOI: 10.1007/s00572-001-0144-7
|View full text |Cite
|
Sign up to set email alerts
|

Saprobic potential of Tricholoma matsutake: growth over pine bark treated with surfactants

Abstract: Saprotrophic growth of Tricholoma matsutake isolates was investigated over Pinus densiflora bark fragments either on soil or on agar media. Preferential colonization of pine bark fragments by hyphae, in glucose-deprived environments suggested that Matsutake was able to extract some nutrients to sustain its growth. This was confirmed in glucose-free liquid nutrient medium, where bark as sole carbon source significantly stimulated (up to two-fold) growth of T. matsutake isolates. The addition of surfactants (Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Numerous studies have highlighted the importance of culture medium on in vitro fungi development (Hung and Trappe, 1983;Brundrett et al, 1996;Vaario et al, 2002). However, the results reported by several authors for different species of Suillus are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the importance of culture medium on in vitro fungi development (Hung and Trappe, 1983;Brundrett et al, 1996;Vaario et al, 2002). However, the results reported by several authors for different species of Suillus are inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…This study detected significantly higher activities of ␤-glucosidase and xylosidase in Shiro ϩ soil than in nearby Shiro Ϫ soil sampled immediately after sporocarps were harvested. Many root tips in Shiro ϩ soil showed signs of necrosis, which is a typical response of the host plant to colonization by T. matsutake (8,26) (45) showed that T. matsutake mycelium invaded the xylem cell walls of pine sawdust and how this fungus was able to produce ␤-glucosidase when pine bark was used as a substrate in vitro (19,44). Within Shiro ϩ soil, the products degraded from cellulose or hemicellulose by matsutake itself and other Shiro ϩ microbes would be important carbon sources for subsequent growth.…”
Section: Discussionmentioning
confidence: 99%
“…Hemicellulotic carbohydrates decrease rapidly during the early stages of decomposition (35). Moreover, matsutake mycelium produces ␤-glucosidase, an enzyme that hydrolyzes oligosaccharides having a ␤-1,4 linkage when incubated on pine bark or even in pure cultures (19,44). These in vitro studies indicate that T. matsutake is able to directly degrade and mobilize certain sources of organic carbon.…”
mentioning
confidence: 95%
“…Numerous studies have been performed on the cultivation of mycorrhizal fungi (Melin and Norkrans 1948;Mikola 1948;Norkrans 1950;Melin 1954Melin , 1959Jayko et al 1962;Lundeberg 1970;Hacskaylo 1973;Molina and Palmer 1982;Fries 1983;Hung and Trappe 1983;Harley and Smith 1983;Ohta 1990;Finlay et al 1992;Mischiati and Fontana 1993;Brundrett et al 1996;Keller 1996;Vaario et al 2002), including studies on the utilization of carbon sources (Ferry and Das 1968;Palmer and Hacskaylo 1970), nitrogen sources (Melin and Norkrans 1948;Norkrans 1953;Finlay et al 1992;Keller 1996), the effect of phosphate on the availability of glucose (Giltrap and Lewis 1981), the effect of chitin (Hodge et al 1995), and the effect of small amounts of glucose on the utilization of other carbon sources (Lamb 1974).…”
Section: Introductionmentioning
confidence: 98%